When is a soil remediated? Comparison of biopiled and windrowed soils contaminated with bunker-fuel in a full-scale trial - Coulon, Frederic; Al Awadi, Mohammed; Cowie, William; Mardlin, David; Pollard, Simon J. T.; Cunningham, Colin; Risdon, Graeme C.; Arthur, Paul; Semple, Kirk T.; Paton, Graeme I. (Elsevier, 2010)
A six month field scale study was carried out to compare windrow turning and biopile techniques for the remediation of soil contaminated with bunker C fuel oil. End-point clean-up targets were defined by human risk assessment and ecotoxicological hazard assessment approaches. Replicate windrows and biopiles were amended with either nutrients and inocula, nutrients alone or no amendment. In addition to fractionated hydrocarbon analysis, culturable microbial characterisation and soil ecotoxicological assays were performed. This particular soil, heavy in texture and historically contaminated with bunker fuel was more effectively remediated by windrowing, but coarser textures may be more amendable to biopiling. This trial reveals the benefit of developing risk and hazard based approaches in defining end-point bioremediation of heavy hydrocarbons when engineered biopile or windrow are proposed as treatment option. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Bunker fuel; Windrows; Biopiles; Bioremediation; Soil ecotoxicology